Applying systems biology to biomedical research and health care: a précising definition of systems medicine - Schleidgen, Sebastian; Fleischer, Henrike; Schickhardt, Christoph; Winkler, Eva C. (BMC health services research, 2017)
Systems medicine has become a key word in biomedical research. Although it is often referred to as P4-(predictive, preventive, personalized and participatory)-medicine, it still lacks a clear definition and is open to interpretation. This conceptual lack of clarity complicates the scientific and public discourse on chances, risks and limits of Systems Medicine and may lead to unfounded hopes. Against this background, our goal was to develop a sufficiently precise and widely acceptable definition of Systems Medicine.
Gesehen am 01.12.2017